Re-imagining the Classroom through Social Justice Projects: Portraying Student´Attitudes - Chaves, Olga (2015)
This paper analyses Costa Rica college EFL learners' attitudes and challenges when conducting social awareness projects as an initiative in an English course. The Think, Share and Act (TSA) project was initiated in January, 2009 with 57 students from different major at Universidad Nacional de Heredia. The students worked for about three months in planning and conducting the project in different settings. Students are given  the opportunity to learn about different global issues, reflect on and discuss them, share their knowledge and experiences related to these concerns and even come up with possible action plans for social problems. The research concludes that these projects heighten interest in researching solcial issues, enhance social and linguistic skills and improve problem solving and leardership skills which grow levels of motivation to carry out humanitarian projects.